Strategi Pendidikan STEM dalam Meningkatkan Keterampilan Pemecahan Masalah di Sekolah Menengah - Greget Widhiati; Widya Aryani (CV. Aksara Global Akademia, 2023)
This study examines the effectiveness of STEM (Science, Technology, Engineering, and Mathematics) education in enhancing problem-solving skills among high school students. With the increasing demand for critical thinking and problem-solving abilities in the workforce, STEM education has become a crucial approach to preparing students for future challenges. The study aims to evaluate how project-based STEM curricula impact students' creativity, analytical skills, and overall problem-solving capabilities. Using a quasi-experimental design with a control group, the research was conducted with high school students who participated in STEM-based lessons involving the 5E instructional model. Data collection involved pre- and post-tests, classroom observations, and semi-structured interviews to measure changes in student skills. The findings indicate that students exposed to STEM education demonstrated significant improvements in problem-solving, creativity, and analytical thinking compared to their peers in traditional lecture-based classes. The study highlights the advantages of project-based learning in promoting active student engagement and fostering skills necessary for addressing real-world problems. These results suggest that STEM education can be more effective than traditional methods in cultivating essential 21st-century skills. The study recommends the broader implementation of STEM strategies in secondary education and further exploration of the long-term impact of STEM learning on various skills required in the professional world.